2013
DOI: 10.1155/2013/105919
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for Chronic Low Back Pain: A Meta‐Analysis of Randomized Controlled Trials

Abstract: The results of the present study indicate that yoga may be an efficacious adjunctive treatment for CLBP. The strongest and most consistent evidence emerged for the short-term benefits of yoga on functional disability. However, before any definitive conclusions can be drawn, there are a number of methodological concerns that need to be addressed. In particular, it is recommended that future RCTs include an active control group to determine whether yoga has specific treatment effects and whether yoga offers any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 49 publications
4
106
0
1
Order By: Relevance
“…Previous research found positive effects after yoga treatment on, e.g., functional measurement scores, balance, flexibility, (pain-related) disability, pain, medication usage, and depression in patients with chronic lower back pain [14][15][16][17][18][19][20][21][22][23][24]. However, the number of randomized clinical studies (RCTs) is small and previous studies reported significant limitations [17,22,24]. In 2007, yoga was already implemented by the American College of Physicians and the American Pain Society [25] in clinical guidelines for clinicians who deal with patients affected by lower back pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found positive effects after yoga treatment on, e.g., functional measurement scores, balance, flexibility, (pain-related) disability, pain, medication usage, and depression in patients with chronic lower back pain [14][15][16][17][18][19][20][21][22][23][24]. However, the number of randomized clinical studies (RCTs) is small and previous studies reported significant limitations [17,22,24]. In 2007, yoga was already implemented by the American College of Physicians and the American Pain Society [25] in clinical guidelines for clinicians who deal with patients affected by lower back pain.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have to include active control groups to determine specific treatment effects and to identify advantages compared to traditional exercise programs and other alternative therapies [17]. It is possible that yoga or eurythmy therapy may be better accepted or more beneficial than physiotherapy-based interventions as they include a mental activating and relaxing focus that specifically enhances stress reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Toplumda sık karşılaşılan bu sağlık problemi için hastalar farklı tedavi yöntemleri uygulayabilmektedir. Uzak Doğu'da özellikle kullanılan manuel terapi, akupunktur, spinal manuplasyonlar, yoga geleneksel ağrı kontrolü yöntemleri olarak kullanılmış ve geniş serilerle yapılan yayınlarda ağrı kontrolünde etkinlikleri kanıtlanmıştır (8)(9)(10). Bununla birlikte özellikle bölgemizde yöresel-geleneksel inanışlara bağlı uygulamalar da azımsanmayacak kadar çoktur.…”
Section: Discussionunclassified
“…In addition, yoga applications contribute to improving muscle strength and flexibility, blood circulation, oxygen consumption and hormonal functions [13]. Studies have shown that, yoga has been used in an efficient manner in respiratory problems, cancer, rheumatoid arthritis, autism, depression, obesity, diabetes, kidney diseases, hemophilia and gastrointestinal disorders [ 14,15]. The effect of yoga on motor function, emotional state and cognitive function has been shown on adults along with children [16,17].…”
Section: Introductionmentioning
confidence: 99%